Knowledge, Attitude, and Practice of Resin Composite Repair among Libyan Practitioners - Elsharkasi , Marwa M. O. (Scientific Journal of University of Benghazi, 2021)
Aim: To examine the contemporary knowledge, attitude and practice of resin composite repair procedures among dental clinicians in Benghazi – Libya. Methods: A survey questionnaire, which consisted of twenty questions, was designed and distributed electronically to 270 graduated dentists in Benghazi - Libya. The questions sought information in relation to the knowledge, attitude and practice of the repair procedures for defective resin composite restorations. Results: The survey response rate was 94%. The findings of the study showed that 143 (56.3%) of the participants were taught about resin composite repair during undergraduate, postgraduate studies, or from other sources. The respondents indicated that the most common indication for composite repair was secondary caries (24.8%) followed by fracture of restoration (18.5%), partial loss of restoration (18.1%), discoloration (17.3%), defective margin, and defective contour (9.1%). Moreover 71% of the participants performed composite repair in dental clinics. The study results revealed that the majority of the dentists (72%) considered the repaired composite restoration as a permanent filling. Most of the participants (43.3% strongly agreed, 43.7% agreed) in Benghazi believed teaching of composite repair technique should be included in the academic curriculum. In conclusion, resin composite repair is a well-established procedure among Libyan practitioners in Benghazi, which is considered a legitimate alternative to total restoration replacement.